Сибирь: [роман ; 16+] / Георгий Марков - Марков Георгий Мокеевич (Сибириада, 2013)
Экземпляры: с/ф № 8 (20151118) / Инвентарный номер: 44075 / Цена: / Авт.знак: М 27 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)